Relative age effect (RAE) of triathletes at the Youth Olympic Games and Qualifiers - Timmerman, W.; van Eemeren, L.; Verachtert, R.
This correlation research searched for trends at high-level competition, Youth Olympic Games and Qualifiers, in triathlon for the 16 and 17-year-old age group men and women. With data of 224 athletes (129 men and 95 women, response grade = 33,5%) there was a weak but significant trend for the male and none for the female. This suggests there can be a relative age effect in triathlon and national federations need to be attentive and take it into account.